Power to the Principals! An Experimental Look at Shareholder Say-On-Pay Voting - Krause, Ryan; Whitler, Kimberly A.; Semadeni, Matthew (Academy of Management Journal, 2014)
With recent legislation mandating that publicly traded corporations submit their CEOs' compensation for a nonbinding shareholder vote, a systematic understanding of shareholder preferences has never been so important. In spite of this, relatively little is known about what impacts shareholders' preferences and, subsequently, their ultimate voting behavior. We integrate two theories to help frame the question and to help predict shareholder behavior. Per agency theory, shareholders, as principals, will disapprove of high CEO rewards and poor firm performance, symmetrically assessing gains and losses. Per prospect theory, shareholders will be loss averse, responding much more strongly to being in a loss position than to being in a gain or neutral position. We combine these theories' predictions in two lab experiments in which we simulate a shareholder “say-on-pay” vote, hypothesizing that shareholders will be concerned with agency costs, but only when they are in a loss position. The results of these simulated votes suggest that shareholders do value “pay for performance,” in keeping with agency theory. However, shareholders exhibit this focus on agency-normative prescriptions asymmetrically, showing loss aversion in keeping with prospect theory. This finding has significant implications for both theory and practice as shareholder votes become a regular and high-profile occurrence.